문학을 활용한 통합영어수업의 학습자 그룹저널에 나타난 공감성 분석 - 최민주(Minju Choi); 김정렬(Jeong-ryeol Kim) (한국콘텐츠학회 논문지, 18(3), 2018)
The aim of this study was to analyze the empathy represented in the learners' group journal of integrated English class using literature. 15 high school students participated in this class. In this study, integrated English class using literature was carried out by supplementing the point that amount of the English classes using literature had been focused on reading activities. In addition, not only communicative abilities but also learners' empathy to the main character in the literary was taught. In order to analyze the empathy expressed in learners' group journal, the integrated English class using literature was conducted in the second period and the class was recorded by video. The empathy was based on the community competence mentioned in the 2015 revised curriculum, and learners were asked to write the group journal. As a result of the research, the learners showed an understanding of the context in the novel and learners' group journal showed that their empathy to the main character in the novel. It is expected that the data on the empathy represented in the learner group journal of the integrated English class using literature will be used in English class. 본 연구는 문학을 활용한 통합영어수업의 학습자 그룹저널에 나타난 공감성을 질적으로 분석하였다. 본 연구는 충북소재 K고등학교 2학년 1개의 반에 속한 15명의 고등학생(남학생 2명, 여학생 13명)을 대상으로 하였다. 본 연구에서는 기존의 문학을 활용한 영어 수업의 다수가 읽기지도에 치중한 점을 보완하여 통합영어수업을 진행하였으며 의사소통능력뿐만 아니라 학습자가 문학작품에서 주인공이 처한 상황에 학습자가 직접 공감하도록 수업을 진행하였다. 학습자의 공감성을 분석하기 위해 2차시에 걸쳐 통합영어수업을 진행하고 진행된 수업을 비디오로 녹화하여 전사하였다. 공감성은 2015 개정 교육과정에서 언급한 공동체 역량에 근거하여 기준을 세웠으며 학습자들로 하여금 주인공의 입장에서 그룹저널을 쓰도록 하였다. 학습자의 그룹저널을 분석한 결과, 학습자들은 소설 속 시대 상황에 대한 이해를 보였다. 또한 현재 자신의 모습을 소설 속 주인공의 모습에 투영하는 모습을 보였다. 같은 주인공의 입장에서 글을 썼지만 각 조마다 공감하는 부분이 상이했으며 작품 속 인물의 내면세계에 대해 공감하는 모습을 확인할 수 있었다. 이러한 문학을 활용한 통합영어수업의 학습자 그룹저널에 나타난 공감성에 대한 분석 자료는 차후 문학을 활용한 수업에 활용될 것으로 기대된다.